(untitled) (Dhaka University Journal of Science, 2012)
A one-pot synthesis of 3, 3-Dimethyl-7, 11-diphenyl-spiro [5, 5] undecane-1, 5, 9-triones 4a-c has been achieved by the application of Michael reaction between dimedone (5,5-dimethylcyclohexane-1,3-dione) 1 and trans,trans diarylideneacetones [1,5-diaryl-1,4- pentadien-3-ones] 2a-c (a. Ar = C6H5-, b. Ar = 2-Cl-C6H4-, c. Ar = 2- CH3O- C6H4) using Lewis acid catalysts. DOI: http://dx.doi.org/10.3329/dujs.v60i1.10349 Dhaka Univ. J. Sci. 60(1): 121-124 2012 (January)